Appliquer les catégories d’observation discursives pour décrire les interactions dans les forums de discussion - Górecka, Joanna (Studia Romanica Posnaniensia, 2017)
The paper presents the objectives, the scenario and the conclusions of an exploratory action-research whose aim was to determine how the descriptive categories elaborated in the field of discourse analysis can be used to explain and to explore the genre of online discussion in public internet forums in the context of foreign language learning. I discuss first a list of descriptive categories elaborated in my research in the form of an observation grid in order to outline the genre specificity of online discussion. Then I describe the application of the observation grid in my research.